2010
DOI: 10.1242/jcs.062810
|View full text |Cite
|
Sign up to set email alerts
|

CXCR7 is an active component of SDF-1 signalling in astrocytes and Schwann cells

Abstract: SummaryThe alternative SDF-1 (stromal cell derived factor-1) receptor, CXCR7, has been suggested to act as either a scavenger of extracellular SDF-1 or a modulator of the primary SDF-1 receptor, CXCR4. CXCR7, however, also directly affects the function of various tumor-cell types. Here, we demonstrate that CXCR7 is an active component of SDF-1 signalling in astrocytes and Schwann cells. Cultured cortical astrocytes and peripheral nerve Schwann cells exhibit comparable total and cell-surface levels of expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 58 publications
3
49
0
Order By: Relevance
“…S3); in particular, stromal cell-derived factor-1 (SDF-1) demonstrates a trend similar to that observed with SC. Recently, it was demonstrated that the SDF-1 receptor, CXCR7, is an active component of SDF-1 signaling in SC [55], suggesting a possible autocrine mechanism. However, further investigation is necessary to identify the precise signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…S3); in particular, stromal cell-derived factor-1 (SDF-1) demonstrates a trend similar to that observed with SC. Recently, it was demonstrated that the SDF-1 receptor, CXCR7, is an active component of SDF-1 signaling in SC [55], suggesting a possible autocrine mechanism. However, further investigation is necessary to identify the precise signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Like MIP-2, CXCL12 can also activate PI-3-K, ERK and cAMP-dependent transcription factor CREB survival pathways in neurons that may afford neuroprotection (Floridi et al, 2003; Lu et al, 2009; Sengupta et al, 2009; Wu et al, 2009). Activation of the chemokine receptor CXCR7 by CXCL12 also activated PI-3-K and ERK pathways that may stabilize the survival of astrocytes when challenged by neurotoxic agents like Aβ (Odemis et al, 2010). Loss of ADAM17 upon Aβ treatment seen in our study is in agreement with observed decreased levels of ADAM17 in AD (Bernstein et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of the CXCL12-CXCR4/CXCR7 axis as a novel therapeutic target led to development of several therapeutic approaches [248, 278]. Examples of these are the anti- CXCR4 drug AMD3100 [279], the CXCL12 analog CTCE-9908 [280, 281, 282], the anti-CXCL12 aptamer NOX-A12 [283], the inhibitor of CXCR4 expression chalcone 4 [284], and the CXCR7-specific inhibitors CCX2066 [278, 283], CCX733 [285] and CCX754 [286, 287]. CXCR4 also has been targeted using monoclonal antibodies and small molecule antagonists [288291].…”
Section: Therapeutic Targetsmentioning
confidence: 99%